Cover Image. Issue 12 (December 2016) - Banerjee, Soumya; Toral, Marcus; Siefert, Matthew; Conway, David; Dorr, Meredith; Fernandes, Joyce
Abstract : Cover: The cover image, by Soumya Banerjee et al., is based on the Research Article dHb9 expressing larval motor neurons persist through metamorphosis to innervate adult‐specific muscle targets and function in Drosophila eclosion, DOI:10.1002/dneu.22400 .